Mega-trends in the Southern African region - Lipper, Leslie; Benton, Tim G. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This study aims to describe recent developments in the Southern African region by documenting a set of mega-trends defining social, economic, political and environmental conditions. It includes analysis of the recent past as well as projections of future trends. To the extent possible, the report is based on information from 2010 to the present, except in some cases where more recent information was not available. The purpose of this analysis is to get a snapshot of current conditions in the Southern African region and the dynamics that generated them, to inform the design and implementation of investments to secure climate-resilient agricultural livelihoods in the region. The study goes beyond simply tracing trends, however, and provides guidance on how the information can best be used in making plans for the future. The mega-trend analysis gives insights into forces that will shape the future but does not provide predictions of the future. Humans are typically very linear thinkers and tend to look at trends from the past and project them forwards into the future, and we often fall into the trap of thinking that the future is defined by what has happened in the past. There is considerable uncertainty over how several of these mega-trends will play out in the near future, with the possibility of major disruptions and changes on the horizon. This can be seen quite clearly in the impact of the COVID-19 pandemic which is still unfolding, and which is already disrupting expectations of future conditions. This uncertainty of future conditions greatly complicates decision-making today. To address this complication, the development of scenarios to identify a range of plausible futures is an important tool for decision-makers. In the final section of the report we give examples of recent scenario work in the region to illustrate how the analysis of megatrends and their uncertainties can be useful in strategic decision-making under uncertainty.